HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI USIA 6-12 BULAN DI DESA SAMBIRESIK KECAMATAN GAMPENGREJO KABUPATEN KEDIRI.pdf - budiman, frenky; Suprihartini, Cucuk (STIKES dan AKZI Karya Husada Kediri, 2024)
Toddler nutritional status is the best indicator to measure community nutritional status. This is because children under five years is prone to nutritional status. The nutritional status of children under five based on the indicator TB / U has a short prevalence (stunting), nationally in 2013 of 37.2% consisting of 18.0% (very short) and 19.2% (short). One of the risk factors for malnutrition and growth inhibition for children under five years is low level of exclusive breast milk. The purpose of this study was to determine the relationship between the history of exclusive breastfeeding and infant nutrition status (PB / U) aged 6-12 months in Sambiresik Village, Gampengrejo District, Kediri Regency.This study was an observational study using the cross sectional method. The population in this study were all mothers who have babies aged 6-12 months in Sambiresik Village, Gampengrejo District, Kediri Regency with a total of 34 mothers and the sample of this study was determined through Simple Random Sampling with a total of 32 respondents. Data were analyzed using the Spearman Rank test. Most of the infants in Sambiresik Village, Gampengrejo Subdistrict, Kediri District, received 17 exclusive breastfeeding (53.1%) and most of the babies had normal nutritional status (PB / U) that was 22 respondents (68.8%).Based on the Spearman Rank Test results obtained that if there was no relationship between the history of exclusive breastfeeding with nutritional status (PB / U) in infants aged 6-12 months with p-value> α (0.154> 0.05). From the results of the study found that there was no relationship between the history of exclusive breastfeeding with the nutritional status of baby (PB / U) aged 6-12 months in Sambiresik Village, Gampengtejo District, Kediri Regency and the results of this study are expected to be able to provide suggestion for mothers to give exclusive breast milk for babies aged 6-12 months.